Financing Global and Regional Public Goods Through ODA Analysis and Evidence from the OECD Creditor Reporting System - Reisen, Helmut (OECD Development Centre Working Papers, 2004)
The present level of ODA falls short of the amount needed to finance the Millennium Development Goals (MDGs). The figure of additional $50 billion per year, roughly the present total of ODA spent by DAC donors, is often quoted (e.g. by the Zedillo Report); it results from the sum of the fight against communicable diseases ($ 7-10 billion), primary schooling ($10 billion), infant and maternal mortality ($12 billion) and halving world poverty ($20 billion). The scarcity of public resources raises the importance of investing in international public goods as the cost of lifting one person out of income poverty, for example through agricultural research and global trade expansion, is estimated to be much lower than the cost of the same impact through traditional aid to poor countries. This raises important issues for donor strategies, in particular principles of aid allocation, which this paper aims to address. First, should aid be partly earmarked towards international public goods? ...